Pengembangan pembelajaran blended learning pada generasi Z - Agus Purnomo; Nurul Ratnawati; Nevy Farista Aristin (Universitas Negeri Malang, 2016)
Every generation has beliefs, values, cultures, perspectives, interests, and different skills for life and work. The generation born in the early 2000s when the rapid development of such technology referred to as generation-z or net generation. Characters of this generation is very sensitive to technology and communication, meaning they have an advantage in the field of information and knowledge development. While the educators who were born in an earlier era are still not familiar with it so that educators often claimed to be